2022
DOI: 10.21147/j.issn.1000-9604.2022.02.04
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an optimized CTC detection model consisting of EpCAM, MUC1 and WT1 in epithelial ovarian cancer and its correlation with clinical characteristics

Abstract: Objective Emerging studies have demonstrated the promising clinical value of circulating tumor cells (CTCs) for diagnosis, disease assessment, treatment monitoring and prognosis in epithelial ovarian cancer. However, the clinical application of CTC remains restricted due to diverse detection techniques with variable sensitivity and specificity and a lack of common standards. Methods We enrolled 160 patients with epithelial ovarian cancer as the experimental group, and 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 64 publications
(64 reference statements)
1
14
0
Order By: Relevance
“…The EPithelialImmunoSPOT (EPISPOT) assay (which exploits tumor expression of specific molecules) allows blood detection of even a single cell and has produced significant results in terms of cell concentration assessment in several solid tumors [ 68 , 69 ]. The assay discriminates tumor cells from “normal” cells by selectively recognizing the expression of the epithelial cell adhesion molecule (EpCAM) [ 70 ]. Unlike other solid tumors, such as adenocarcinomas of the colon and pancreas and hormone-refractory adenocarcinomas of the prostate, melanoma has non-high levels of EPCAM protein [ 71 , 72 ].…”
Section: Liquid Biopsy (Lb): An Overviewmentioning
confidence: 99%
“…The EPithelialImmunoSPOT (EPISPOT) assay (which exploits tumor expression of specific molecules) allows blood detection of even a single cell and has produced significant results in terms of cell concentration assessment in several solid tumors [ 68 , 69 ]. The assay discriminates tumor cells from “normal” cells by selectively recognizing the expression of the epithelial cell adhesion molecule (EpCAM) [ 70 ]. Unlike other solid tumors, such as adenocarcinomas of the colon and pancreas and hormone-refractory adenocarcinomas of the prostate, melanoma has non-high levels of EPCAM protein [ 71 , 72 ].…”
Section: Liquid Biopsy (Lb): An Overviewmentioning
confidence: 99%
“…Haematogenous spread of cancer cells in ovarian carcinomas is believed to be a rather rare event. Still, this phenomenon is well documented [ 7 , 8 , 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 23 , 24 , 26 , 32 , 43 , 50 , 69 , 70 , 71 ], and the presence of CTCs in blood was recently shown to correlate with tumor stage, presence of ascites, tumor debulking, disease recurrence, shorter OS and PFS [ 7 , 18 , 23 , 24 , 43 , 50 , 69 ].…”
Section: Clinical Relevance Of Ctcs In Ovarian Cancermentioning
confidence: 99%
“…A number of studies have also evaluated the utility of CTCs as a biomarker of chemotherapy response in OC [ 7 , 11 , 12 , 18 , 43 , 69 , 71 ]. It has been demonstrated that chemotherapy leads to a rapid decline in CTCs count.…”
Section: Clinical Relevance Of Ctcs In Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The significant heterogeneity of EOC primary tumors makes it more challenging to isolate CTCs from EOC patients’ blood, especially since EOC CTCs are highly heterogeneous with variable expression levels of epithelial cell adhesion molecule (EpCAM). , Moreover, CTCs that undergo the epithelial-to-mesenchymal transition (EMT) progress may lose EpCAM expression, further complicating the isolation of EOC CTCs by traditional EpCAM-dependent methods. To overcome the issue, our group , and others have developed a multimarker capture strategy targeting multiple surface proteins for EOC CTC isolation, including N-cadherin ,, and other epithelial cell surface antigens, e.g., MUC1 . N-cadherin is a marker of mesenchymal phenotype associated with the EMT, which is known to play a critical role in tumor invasion in several cancer types, including ovarian cancer …”
mentioning
confidence: 99%